The Selfless Mind. Personality, Consciousness and Nirvana in Early Buddhism. Peter Harvey. - Bodhi, Bhikkhu (Buddhist Studies Review, 1997)
The Selfless Mind. Personality, Consciousness and Nirvana in Early Buddhism. Peter Harvey. Curzon Press, Richmond 1995. 293 pp. Cloth £40.00, paper £14.00. ISBN 0 7007 0337 3, 0 7007 0338 1.